1999
DOI: 10.1055/s-1999-14081
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Standardized Panax ginseng Extract on the Skeletal Muscle of the Rat: A Comparative Study in Animals at Rest and Under Exercise

Abstract: The effect of standardized Panax ginseng extract G115 on enzymatic activities, myotypological composition, capillaries and mitochondrial content was studied in the skeletal muscle of male rats Wistar. Simultaneously to the G115 administration the rats performed exercise. The animals were divided into 4 groups. The dose of the ginseng extract G115 was 50 mg/kg. The length of the experimental period was 12 weeks. After 24 hours of inactivity the muscles of the hindlimb were extracted. With regard to the enzymati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…P. ginseng extract is known to increase capillary density and the oxidative capacity of muscles with greater aerobic potential (30). Acute pre-treatment of mice with crude extract increased their endurance in the swimming and running tests, but the reason for this increase was linked to the availability of muscle substrates and their utilization (31).…”
Section: Soleusmentioning
confidence: 99%
See 1 more Smart Citation
“…P. ginseng extract is known to increase capillary density and the oxidative capacity of muscles with greater aerobic potential (30). Acute pre-treatment of mice with crude extract increased their endurance in the swimming and running tests, but the reason for this increase was linked to the availability of muscle substrates and their utilization (31).…”
Section: Soleusmentioning
confidence: 99%
“…These activities are focused on mitochondria as the major site of free radical generation. Ferrando et al (30) showed that ginseng extract increased mitochondrial density in rat oxidative muscles after a 50-mg/kg dose for three months. On the other hand, down-regulation in CS activity has been reported in muscle and liver measured by GSH depletion and mitochondrial oxidative damage (33).…”
Section: Soleusmentioning
confidence: 99%
“…Many studies have been made with this extract from PG, but the effectiveness of this plant still needs to be proven, due to the large number of investigations have not shown any effect in increasing physical performance with humans (Scaglione et al, 2005). Fernando et al (1999) showed in their research a raise in capillary density and muscle mitochondrial content of mice, suggesting that prolonged treatment with G115 (50mg/kg for 12 weeks) improve the aerobic output and therefore the physical performance (Ferrando et al, 1999). Research such as Engels et al (2001), executed with double-blind trials (placebo group and G115 group) with active women, showed no significant changes in peak anaerobic power, anaerobic power average, fatigue and post-exercise recovery after supplementation (Engels et al, 2001).…”
Section: Volume 8 | Issue 4 | 2013 | 1058mentioning
confidence: 97%
“…RG contains various ginsenosides, 20(S)-protopanaxadiol and 20(S)-protopanaxatriol, and has been widely used as an ergogenic aid. Although only one human study has found an association between RG intake and exercise performance (1), several rat studies have demonstrated a positive association between RG intake and exercise performance (2)(3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%